Hydrogels Powered by Nanoemulsion Technology for the Topical Delivery of Acmella oleracea Extract - Eleonora Spinozzi; Marco Cespi; Marta Ferrati; Riccardo Petrelli; Filippo Maggi; Junbiao Wang; Sunday Segun Alimi; Diego Romano Perinelli; Giulia Bonacucina (Pharmaceutics)
Background/Objectives: Natural products are gaining increasing importance due to the large variety of biological activities exerted by their constituents. Among these, the products deriving from Acmella oleracea (L.) R.K. Jansen can be exploited for their local anaesthetic, myorelaxant, anti-inflammatory/analgesic, and antifungal properties. In this regard, there is a need to develop novel formulations for the topical delivery of A. oleracea-derived extracts to widen their use in the pharmaceutical and cosmetic fields. Methods: Nanoformulations, i.e., nanoemulsions (NEs) and microemulsions (MEs), were investigated as a strategy to encapsulate an extract from A. oleracea at the nanoscale level in water and then incorporated into xanthan gum-based hydrogels. Results: Only NEs provided a physically stable formulation, while the precipitation of solid hydrophobic components from the extract was observed during ME preparation under all tested conditions despite the use of ethyl oleate as an oily co-solvent. The optimized NE-based hydrogel remained physically stable over six months, as confirmed by rheological measurements and polarized optical microscope observation, without a phase separation phenomenon. Therefore, NEs resulted more suitable nanodispersed systems than MEs for the encapsulation of A. oleracea extract, which contains a large amount of hydrophobic constituents that are solid at room temperature. Furthermore, the sustained spilanthol release across an artificial membrane (Franz cell apparatus) and the cytotoxic profile on HaCaT cell line support its potential topical application. Conclusions: The outcomes of this study provided valuable insights into the formulation of A. oleracea extract, broadening its fields of applicability, including topical administration.